The social discourses on market-based instruments to manage non-point-source water pollution in the Oldman River basin, southern Alberta. Issue 3 (3rd April 2018) - Kerr, Gillian; Bjornlund, Henning
ABSTRACT: The Canadian province of Alberta has incorporated market-based instruments into recent policy to manage non-point-source pollution. Investigating context-specific social discourses through the Q-method provides a timely understanding of why these instruments have not been well implemented in southern Alberta, and may assist in developing their potential. This article identifies four distinct discourses, named Incentive Orienteers, Rural Advocates, Honest Brokers and Progressive Producers.